Chapter 2 The state of governance in Africa - FOMBAD, CHARLES (Taylor & Francis, 2023)
Good governance is a critical factor in shaping the level of peace and stability in any country as well as influencing the prospects for its economic development. African governance trends were supposedly transformed by the dramatic reforms introduced by almost all countries at the end of the Cold War in the 1990s. Most commentators were optimistic that a new era of good governance and constitutionalism had set in. Now, three decades since these reforms were undertaken, are they bearing fruit? Have the prospects for political stability, peace and economic development been enhanced? In reviewing the state of governance, this chapter examines good-governance initiatives introduced in the 1990s by African governments and reinforced by several instruments adopted to this end by the African Union and Regional Economic Communities. Against this background, the chapter examines a number of continental and global good-governance indicators to see what they tell us about the state of governance in the continent today. The chapter concludes that unless the existing framework for constitutionalism, good governance, and respect for the rule of law are reimagined and reinforced, Africa will continue to lag behind in social and economic development while political instability will increase.